STUDY ON THE COMPOSITION OF NPK FERTILIZER AND GOAT MANURE ON THE GROWTH AND YIELD OF SWEET CORN (Zea mays Saccharata Sturt. L) - Santoso, Sartono Joko; Triyono, Kharis; Maulida, Elly Istiana (jfpublisher, 2025)
In agricultural cultivation technology, there are various determining factors that greatly affect plant growth and yield. One important factor in agriculture is fertilization. This study aims to examine the effect of NPK fertilizer composition and goat manure on the growth and yield of sweet corn plants. This research was conducted from June 10, 2024 to September 16, 2024 at Jaya Wijaya Experimental Farm, Mojosongo, Surakarta, at an altitude of 400 meters above sea level with Latosol soil type. This study used a Completely Randomized Group Design (CRD) with two treatment factors, NPK fertilizer and goat manure, each repeated three times to obtain 48 treatment combinations. The parameters observed included plant height, number of leaves, cob diameter, cob weight with husk, and cob weight without husk. The results of the experiment showed that the addition of NPK fertilizer significantly affected the growth and yield of sweet corn plants, while the addition of goat manure and the interaction between the two did not give any significant effect.